Land Charges in Fund Loan Agreements with Uncertified Land Guarantee is Linked to Law No. 42 of 1999 Concerning Fiduciary Guarantees - Wira Franciska (JURNAL AKTA, 2024)
With the exit of Act Number 6 Year 1996 concerning Rights Responsibility of Land Ground Along with Objects related to Land Ground, Rights Responsibility is the single guarantee institute of land; ground. Object Rights Responsibility is obliged to enlist beforehand or have. Lower him ability of land owner debtor economics which is not yet certified, whereas certificate expense which is relatively costly, requires a guarantee institute which does not oblige guarantee object enlisted before hand. Fiduciary as guarantee institute expected to be able to overcome the problems. Fiduciary has gone into effect as guarantee institute of land; ground which not yet. This matter can be seen in Decision Appellate Court Number 3216/K/Perd/1984 28 July 1986 contending that land following house which in of unclear him of rights status of earning isn't it. This matter becomes a new problem which requires to look for soybean cake how legal consequences that happened when this moment there is an agreement of guarantee of fiduciary with land ground guarantee object which not yet.